Customer loyalty in financial services from a service-dominant logic perspective / Kat Mui Ling - Kat, Mui Ling (2010)
Purpose – Modern customers are now more informed, connected, and active in their consumption activities. As a result, it is becoming increasingly common for consumers to jointly create value with the firm to satisfy their personalised demand. The purpose of this research is to investigate the effect of involving customer as active participants in the co-production of consumption experience and co-creation of value on customer loyalty in the provision of financial services. Design/methodology/approach – The hypotheses were tested by using regression analysis on data collected from a survey that yielded 285 respondents who are the customers of various unit trust companies in Malaysia. Findings – The findings show that there is a significant and positive relationship between value co-creation and customer loyalty. It displays that customer experience mediate the relationship between value co-creation and customer loyalty, and attitudinal loyalty mediates the relationship between customer experience and behavioural loyalty. Practical implications – Value co-creation is an important strategy for financial services provider to find innovative ways to differentiate themselves and foster customer loyalty in the increasingly competitive marketplace. Original/value –This research binds together value co-creation and customer loyalty in the financial services context which has not been done in prior research. This research also builds empirically evidence to support and validate the concept of value co-creation. Keywords – services marketing, service-dominant logic, value co-creation, customer loyalty, customer experience Paper type – Research paper